State Centralization and the Collapse of Parliamentary Democracy in Indonesia - Haviz, Fauzan; Hendri, Novi; Wirman, Hardi Putra (El-Rusyd, 2025)
This study analyzes the transformation of Indonesia’s political structure from a federal system to a unitary state during the 1950s, with particular attention to center–periphery relations, the emergence of the PRRI and Permesta movements, and their political implications for the configuration of national power. Employing a qualitative approach grounded in historical research, the study utilizes document analysis of state archives, legal and regulatory texts, political speeches, and relevant academic literature. The data are examined through qualitative content analysis and historical interpretation to identify patterns of power centralization, elite fragmentation, and fiscal–political tensions between the central government and regional authorities. The findings indicate that the transition to a unitary state was shaped by a complex interaction of parliamentary political dynamics, unequal resource distribution, and post-election institutional instability. PRRI and Permesta emerged as expressions of regional dissatisfaction with increasing centralization rather than as explicitly separatist movements; however, the escalation of these conflicts contributed to the weakening of parliamentary democracy. The study further demonstrates that the dissolution of the Masyumi Party and the Indonesian Socialist Party (PSI) reflected state-led efforts to consolidate political authority within the framework of Guided Democracy. This research contributes to historical scholarship on center–region relations and the processes of political centralization in postcolonial state formation.